CD68 staining correlates with the size of residual mass but not with survival in classical Hodgkin lymphoma. Issue 5 (May 2015) - Agur, Ariel; Amir, Gail; Paltiel, Ora; Klein, Martine; Dann, Eldad J.; Goldschmidt, Hanoch; Goldschmidt, Neta
Abstract The prognostic role of CD68 tumor-associated macrophages in classic Hodgkin lymphoma (cHL) remains controversial. We stained diagnostic biopsies and scored for CD68 using the PGM1 antibody among 98 consecutive patients with cHL from our center followed over a median of 45 months for progression-free survival (PFS). Among 79 patients we assessed interim and post-treatment positron emission tomography-computed tomography (PET-CT). Residual mass (RM) size was based on the greatest diameter of the largest mass seen in post-treatment imaging, and percent reduction was calculated by comparing RM size with its greatest pretreatment diameter. We found a significant association between CD68 positivity and absolute size of initial disease mass (p = 0.014) and residual mass at the end of therapy (p = 0.006) but no association was observed with interim PET-CT results or PFS. Our findings suggest that macrophages may influence tumor size by altering the microenvironment. This study does not support a prognostic role of CD68 positivity in predicting survival.